2021
DOI: 10.1021/acschemneuro.1c00177
|View full text |Cite
|
Sign up to set email alerts
|

Alizarin and Purpurin from Rubia tinctorum L. Suppress Insulin Fibrillation and Reduce the Amyloid-Induced Cytotoxicity

Abstract: Alizarin (1,2-dihydroxy­anthraquinone) and purpurin (1,2,4-trihydroxy­anthraquinone), natural anthraquinone compounds from Rubia tinctorum L., are reported to have diverse biological effects including antibacterial, antitumor, antioxidation, and so on, but the inhibition activity against amyloid aggregation has been rarely reported. In this study, we used insulin as a model protein to explore the anti-amyloid effects of the two compounds. The results showed that alizarin and purpurin inhibited the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…14 Moreover, alizarin inhibits insulin-induced fibrillation and amyloid-induced cytotoxicity. 15 On the basis of these, it was demonstrated that alizarin has several biological effects including antibacterial, antitumor, antioxidation, and anti-Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…14 Moreover, alizarin inhibits insulin-induced fibrillation and amyloid-induced cytotoxicity. 15 On the basis of these, it was demonstrated that alizarin has several biological effects including antibacterial, antitumor, antioxidation, and anti-Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the degradation species, dehydroascorbic acid and diketogulonic acid, showed a much stronger disruptive effect on mature amyloid fibrils and exhibited less cytotoxicity. Wang et al reported the use of two naturally occurring anthraquinones, alizarin and purpurin, in the disintegration of mature insulin fibrils to shorter ones . TEM imaging and DLS analysis of the samples confirmed the shorter size of fibrils after small molecule treatment compared to untreated insulin aggregates, although the authors did not comment on the cytotoxicity of the degraded products.…”
Section: Prevention Of Insulin Aggregationmentioning
confidence: 99%
“…There are very few known inhibitors of insulin aggregation, like cyclodextrins, 23 natural and synthetic polypeptides, 24–27 epigallocatechin-3-gallate, 28 quercetin, 29 quinones, 30 anthraquinones-alizarin and purpurin, 31 and ascorbic acid. 32 Fibrils once formed are very much stable thermodynamically.…”
Section: Introductionmentioning
confidence: 99%